Identifikasi Morfometrik dan Korelasi Genetik Ayam Jawa Super (Joper) Umur 0-3 Minggu selama Pemeliharaan secara Intensif - Siwi Pratiwi; Yosephine L.R.E Nugraheni; Danes Suhendra (Universitas Tidar, 2023)
The purpose of this study was to examine the morphometric changes of the Joper chicken atthe age 0–3 weeks, the genetic correlation of cross-breeding between domestic cock and purebreedlaying hens, and the morphometric measurement data of the Joper chicken 0–3 weeks old. Dataanalysis uses descriptive analysis. Research results have shown that the growth of Joper chickens aged0–3 weeks has doubled every week. The average of all measurements is body weight (107,5 ± 87,42g), beak length (1,2 ± 0,58 cm), body length (7,1 ± 1,69 cm), height (15,6 ± 6,25 cm), wing length (7,3± 2,35 cm), longest finger length (2,8 ± 0,85 cm), and chest size (10,9 ± 4,82 cm). The genetic correlationvalues between body weight and beak length (-1.314), body weight with body length (-0.029), bodyweight with body height (-0.048), body weight with wing-length (-0.029), weight with height (-0.048),weight with length (-0.014), weight with longest finger-length (-0.08), and weight-length (-0.08).and witha chest ring (-0.038).